Economic performance assessment and monitoring in LP-DMC type controller applications. (September 2017) - Godoy, J.L.; Ferramosca, A.; González, A.H.
Highlights: The LP-DMC type control structure is analyzed in order to clarify the role of each block. It is defined a desired target as a solution of an underlying optimization problem. It is shown that the controller steers the system to this desired target. The underlying problem is used as a benchmark to define key performance indicators. Abstract: One of the main reported problems in petrochemical applications of Linear Programming-Dynamic Matrix Control (LP-DMC) type controllers is their global performance assessment. Since the stationary optimization and dynamic control blocks have not a transparent link between them, it is not easy to find appropriate references to evaluate the overall performance, and more important, to clearly determine the causes of an eventual loss of performance. In this work, the whole LP-DMC problem is analyzed and an off-line underlying optimization problem is defined, whose solution is used as a benchmark for the global closed-loop behaviors study. Based on this idea three global indicators, which evaluate and diagnose poor controller performance, are proposed. The indicators were successfully tested in two case studies: an integrating system and the well-known Shell heavy oil fractionator.